Crowdfunding and Cash Waqf Linked Deposit: A Tech Integrated Model for Sustainable Development - Kurniawan, Muhammad Iman; Akbar, Rifaldi Nurul; Akmal, Aria Nur (Maaliyah: Journal of Islamic Economic Law and Islamic Finance, 2025)
This study analyzes the integration of Crowdfunding and Cash Waqf-Linked Deposits (CWLD) as a technology-based Islamic financial model supporting the Sustainable Development Goals (SDGs). Employing a Systematic Literature Review (SLR) with the PRISMA approach, it synthesizes findings from eight primary articles published over the past five years. The analysis indicates that this integration effectively addresses limitations of conventional cash waqf, such as low public literacy, minimal institutional innovation, and regulatory constraints. Crowdfunding expands the donor base, particularly among younger generations and the Muslim diaspora, via transparent, accountable, and participatory digital platforms. Concurrently, CWLD ensures sustainable benefits by adhering to capital preservation principles and channeling returns to social, educational, health, and economic empowerment sectors. Digital technologies, especially blockchain, smart contracts, and tokenization, serve as key catalysts for enhancing transparency, accountability, and fund management efficiency. This hybrid model not only meets financial needs but also fosters public trust, strengthens global Muslim solidarity, and promotes Islamic financial inclusion. Significant challenges remain, including cross-jurisdictional regulatory limits, cybersecurity risks, and low Islamic finance literacy. Therefore, successful implementation depends heavily on institutional innovation, adaptive regulations, and continuous education. This integration represents a structural transformation in the Islamic philanthropy ecosystem, aligning with Maqasid al-Shariah and the requirements of inclusive development in the digital era.